Partial Replacement of Vitamin E with Polyphenol in Nursery Pig Diets - Zhong-Xing Rao; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Apoorva S. Shah; Brandon H. Foley; Karsten C. Kjeldsen; Grete Brunsgaard; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 300 pigs (241 × 600 DNA; initially 13.1 lb) were used in a 42-d trial to determine the effects of vitamin E levels and partially replacing vitamin E with a polyphenol (Cabanin CSD; R2 Agro, Denmark) on growth performance, complete blood count (CBC), serum thiobarbituric acid reactive substances (TBARS), superoxide dismutase (SOD), and cytokine panel. Sixty pens of pigs were weighed and allotted to 1 of 5 dietary treatments in a completely randomized design with 12 pens per treatment. A control treatment was formulated to provide 15 IU/kg of vitamin E equivalence from vitamin E. This control treatment was then used as a base for 3 replacement strategy diets to determine the effects of replacing an additional 60 IU/kg of vitamin E with Cabanin CSD in diets containing a basal level of vitamin E requirement estimate (15 IU/kg). First, an additional 60 IU/kg of vitamin E was added for a total of 75 IU/kg of vitamin E equivalence. Second, 50% of the additional vitamin E (30 IU/kg) was replaced with the equivalency of Cabanin CSD. Third, all 60 IU/kg of the additional vitamin E was replaced with the equivalency of Cabanin CSD. To evaluate whether there are negative effects of feeding nursery pigs a high level of Cabanin CSD, a fifth treatment was formulated to provide 575 IU/kg of vitamin E equivalence with 75 IU/kg from vitamin E and 500 IU/kg from Cabanin CSD. Whole blood and serum samples were collected on d 10 and 42. For growth performance, increasing vitamin E equivalence tended to improve (quadratic,P<0.10) F/G from d 10 to 21, and tended to improve (linear,P<0.10) F/G from d 21 to 42 and 0 to 42. For antioxidant status, increasing vitamin E equivalence improved (linear,P<0.05) d 42 SOD. For cytokine, there was no evidence of differences (P>0.10) between treatments and vitamin E equivalence. Moreover, there was no evidence of differences (P>0.10) in all response variables between the 3 replacement strategies throughout the entire period. In summary, increasing vitamin E equivalence tended to improve F/G, which may be related to the improved SOD activity. Furthermore, Cabanin CSD can effectively replace vitamin E provided above the vitamin E requirement to provide similar benefits from increasing vitamin E equivalence.
Keywords: antioxidant; growth; nursery pig; polyphenol; vitamin E